The Management and Syllabus of Chinese Tertiary Programs in Malaysia——with special reference to the Chinese Program at Universiti Putra Malaysia - Lay Hoon, Ang; Kai Chee, Lam (New Era Edu Sdn. Bhd., 2020)
Malaysia is renowned for its Chinese education as first language which covers pre-school, primary level, secondary level to higher learning. The higher education in Chinese studies begins to grow only at the end of 20th century. A total of eight private and public universities are offering Chinese studies at bachelor and also postgraduate level. With special reference to Universiti Putra Malaysia, this paper aims to investigate the enrolment administration and the content of the Chinese program. A qualitative analysis is carried out based on the data of bachelor program in Chinese studies, postgraduate program in Chinese literature, and five postgraduate programs on applied linguistics inclusive of Chinese linguistics and culture, namely translation and interpretation, applied comparative linguistics, literary and cultural studies, discourse studies, and literacy studies. The findings indicate that the Chinese education at higher education level has expanded the research scope in Chinese studies which thus complete the chain of Chinese education, covering all levels.